KONCEPCJE SUWERENNOŚCI PAŃSTWA W SFERZE POLITYKI GOSPODARCZEJ W WARUNKACH EUROPEJSKIEJ INTEGRACJI GOSPODARCZEJ - Woś, Jerzy; Hnatyszyn-Dzikowska, Anna (Wydział Prawa i Administracji UAM, 2007)
The objective of the paper is to systemise the contemporary attempts to define state sovereignty, and, in particular, the realisation by a sovereign state of its economic functions in conditions of a tightening economic integration. The authors start by looking at the classic concept of state sovereignty and then confront it with the competences of a state at different stages of European integration and in the Euro zone. Those consideration also include the relation between state sovereignty and the principle of subsidiarity. The paper ends with a description of a contemporary definition of state sovereignty in the area of economic policy.
THEORETICAL CONCEPTS OF STATE SOVEREIGNTY IN ITS ECONOMIC POLICY IN THE EUROPEAN ECONOMIC INTEGRATION